Effect of Carbohydrate Drink Intake Patterns on Exercise in Heat - Shukla, Neeraj; Mittal, Parul; Sandhu, Jaspal S. (Pakistan Journal of Nutrition, 2008)
Carbohydrate drink can increase work capacity by maintaining power output or speed or prolonging the time to fatigue at a fixed workload. Literature is available on fluid intake content and exercise performance. No study has been undertaken till now on fluid intake patterns during high intensity exercise in heat. Therefore the present study is devised to fill this gap and to design an appropriate fluid volume intake pattern during high intensity exercise in hot environmental condition. 15 moderately trained men participated in the study. Each subject was given two different intake patterns of carbohydrate drink in two exercise sessions conducted on different days. A gap of seven days was kept between two exercise sessions. Total amount of fluid intake by the subjects in each session is 1000ml. During the experiment ambient temperature was kept constant at 35°C. Parameters evaluated were blood glucose concentration during and after the high intensity exercise, time to exhaustion and mental concentration. Findings of the present study revealed that when carbohydrate ingestion was done in large quantities before exercise, the rate of glucose disappearance was significantly (t = 10.34, p<0.05) earlier as compared to carbohydrate ingestion intermittently during exercise in hot environmental condition. Time of exhaustion was significantly (t = 13.73, p<0.05) higher in intermittent drink intake pattern. Performance in mental concentration was significantly (t = 4.98, p<0.05) better in intermittent drink intake pattern.